The Effect Of Temperature On The Electrical Conductivity And Microstructure Behaviour Of Silver Particles - Omar, Ghazali; Salim, Mohd Azli; Masripan, Nor Azmmi; Mohd Yunos, Afiqah; Ahmed Al-Mola, Mohammed Hussin (Universiti Malaysia Perlis, 2020)
Silver conductive ink has been used in the electronics industry due to their potential advantages such as high electrical conductivity and thermal conductivity. However, silver needs to undergo a curing process to reduce the porosity between particles as well as to have a smooth conductive track to ensure maximum conductivity. Therefore, the effect of temperature on the electrical conductivity and microstructure were explored. The printing of silver conductive paste was executed on a polymer substrate through screen printing before analysis. Next, an electrical analysis was done to measure the conductivity by using a 4-point probes instrument, followed with microstructure and mechanical analysis which were carried out to observe the structure behaviour and hardness of silver respectively with respect to temperature. The study found that the electrical conductivity of silver increases when temperature elevated. Besides that, the microstructure of silver has a larger size with the increase in temperature, correspondingly cause the silver to have less hardness. In conclusion, temperature plays significant roles in increasing the electrical conductivity of silver.